Keunggulan Tabungan Wadiah dan Mudharabah dalam Perbankan Syariah untuk Menarik Minat Nasabah Berbasis Syariah - Ferdi Gunawan Siagian; M. Zulfikri Suti (Universitas 45 Surabaya, 2025)
This study employs a quantitative method to analyze the advantages of Wadiah and Mudharabah savings in attracting Sharia-based customers. The data used were sourced from 15 journals on Islamic banking and relevant empirical studies. Wadiah savings offer secure deposits without returns, while Mudharabah savings provide competitive profit-sharing benefits. These advantages offer flexible options for customers with varying financial preferences. The findings indicate that both savings types play a crucial role in enhancing Sharia-based financial inclusion. Factors such as trust, Sharia principles, and transparency influence customers’ interest in utilizing these services. The results highlight that product innovation and proper promotion can increase the appeal of Wadiah and Mudharabah savings. Furthermore, the combination of non-material benefits and financial advantages from these two products can encourage community participation in the Islamic banking system. This study recommends Islamic banks prioritize Sharia compliance and customer education to remain competitive in the market.